Single cell transcriptomic analysis reveals transcriptome differences of different cells between eosinophilic chronic rhinosinusitis with nasal polyps and non-eosinophilic chronic rhinosinusitis with nasal polyps - Ying Jin; Yuanshan Liang; Zhijun Wang; Yiting Jiang; Fayang Yuan; Tian Zhang (PLoS ONE, 2025)
Background Chronic rhinosinusitis (CRS) with nasal polyps is a heterogeneous chronic inflammatory disease generally divided into two phenotypes including eosinophilic CRS with nasal polyps (eCRSwNP) and non-eosinophilic CRS with nasal polyps (neCRSwNP). However, its pathogenesis remains largely unknown. The aim of this study was to explore mechanistic differences between eCRSwNP and neCRSwNP using a bioinformatics approach. Methods We comprehensively analyzed single-cell RNA sequencing data from 3 healthy controls and 6 patients with CRSwNP (including 3 with eCRSwNP and 3 with neCRSwNP) to explore the heterogeneity and potential mechanisms of CRSwNP. Results Cluster analysis based on differential gene expression delineated 14 cell clusters. The eCRSwNP group exhibited a markedly higher prevalence of glandular cells and a notable reduction in fibroblasts, myoepithelial cells, and secretory cells compared to patients with neCRSwNP. Functional enrichment analysis of differentially expressed genes revealed the activation of pathways such as IL2-STAT5 signaling and the inhibition of apoptotic pathways in eCRSwNP compared to neCRSwNP. Significant differences in the metabolic profiles of epithelial cell subpopulations were observed between eCRSwNP and neCRSwNP. Furthermore, there were notable discrepancies in the numbers and functionality of immune cells between eCRSwNP and neCRSwNP. The CD4+Th2 cell subsets were found to be significantly enriched in eCRSwNP. The highest number of cellular communications from type 2 conventional dendritic cells (cDC2) to CD4+Th2 cells was found in CRSwNP, where the ICAM1-CD226 pathway from cDC2 to CD4+Th2 was significantly upregulated in eCRSwNP. In addition, eCRSwNP was mainly infiltrated with tissue-resident macrophages, whereas neCRSwNP was mainly infiltrated with monocyte-derived macrophages. Conclusions Our study provides new insights into the heterogeneity, molecular mechanisms, and biomarkers of CRSwNP, contributing to improved diagnostic and therapeutic options for this condition.